Kepadatan Populasi Kepinding Tanah ( Scotinophara coarctata) ( Hemiptera: Pentatomidae) Pada Tanaman Padi Di Rantau Panjang Kecamatan Sasak Ranah Pasisie Kabupaten Pasaman Barat - Wulandari, Fika; Jasmi, Jasmi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACT One of the pests that attack the rice plant is Scotinophara coarctata (Ladybug stink) of the family Pentatomidae, local people know Scotinophara coarctata as bedbug Land. Bedbug soil pests attacking rice plants at the vegetative stage and tillering phase generative, form of attack Scotinophara coarctata in rice plants at tillering fese make rice plants become stunted and the generative fese make grain be empty. Based on this, the study aims to determine the population density of bedbug ground (Scotinophara coarctata) (Hemiptera: Pentatomidae) on rice plants in Rantau Panjang Kecamatan Sasak Ranah Pasisie West Pasaman. In connection with that have done research on bedbug Population Density Land ( Scotinophara coarctata ) (Hemiptera: Pentatomidae) At Rice on 13-14 September 2013. Sampling was conducted in the area Rantau Panjang Kecamatan Sasak Ranah Pasisie West Pasaman Census Method using Paste Trap (Sticky Trap) to Scotinophara coarctata that existed at the study site. Sampling was carried out 2 times on wet soil conditions and the dry land in the morning and afternoon. Generated from research on the wet ground which is obtained by 544 pieces and imago nimpha stadia with an average density of 10.88 and on dry land acquired 475 flat tail - nimpha and adult of average density 9.5. Hopefully in further studies to doing research on how to conduct Scotinophara coarctata on rice plants.